Effects of a naturalistic intervention on the speech outcomes of young children with cleft palate. (2nd September 2020) - Scherer, Nancy J.; Kaiser, Ann P.; Frey, Jennifer R.; Lancaster, Hope Sparks; Lien, Kari; Roberts, Megan Y.
Abstract: Purpose : The purpose of this study was to investigate the extent to which a naturalistic communication intervention, Enhanced Milieu Teaching with Phonological Emphasis (EMT + PE) improved the speech outcomes of toddlers with cleft palate with or without cleft lip (CP ± L) Method : This study was a stratified randomised controlled trial. Setting: Treatment was delivered in a university clinic by a trained speech-language pathologist. Thirty children aged between 15 and 36 months ( M  = 25) with nonsyndromic CP ± CL and typical cognitive development were randomly assigned to a treatment (EMT + PE) or business as usual comparison condition. Participants in the EMT + PE treatment group received 48, 30-min sessions, over a 6-month period. Fidelity of treatment was high across participants. The primary outcome measures were percent consonants correct (PCC), consonant inventory, compensatory articulation errors, and nasal emission. Result : Regression analyses controlling for pre-intervention child characteristics were conducted for PCC and consonant inventory. Intervention was not a significant predictor of post-intervention outcome. Words per minute differentiated the children who benefitted from the intervention from those who did not. Reduction in compensatory errors and nasal emission occurred in both groups but to a greater degree in the EMT + PE group. Conclusion : EMT + PE is a promising early speech intervention for young children with CP ± L, especially for children with higher rates of word use.